Analysis of Strengthening Character Education in Grompol Batik in Soendari Batik Gallery - Regina, Belinda Dewi; Wijayaningputri, Arinta Rezty (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2021)
Character education is an effort to create a generation that is intelligent, has noble character and has an Indonesian personality. The success of character education in learning does not necessarily come from the perspective of the cognitive domain, but rather how to balance cognitive, affective, and psychomotor domains whose estuary is to create a complete human being, likewise with cultural values. Foreign cultural values are growing rapidly along with technological advances, which have significantly shifted local cultural values in Indonesia, one of which is batik, most people, including university students, do not know the uniqueness of local wisdom in their respective regions; this Soendari Gallery has a batik based on strengthening character education. The purpose of this study is how to analyze the content of character education contained in Grombol Batik at the Soendari Gallery. This study uses a qualitative approach with a descriptive type of research. The subject of this research is Grompol Batik from Soendari Gallery. In Grompol batik, there is a circle or oval shape, which is one of the five characters, namely mutual cooperation. Besides that kawung is also known as a symbol of strength and justice which is also one of the dai character education. It can be concluded that the Grompol batik contains character education in it. This research is expected to provide many benefits for the community and the artists.